2002
DOI: 10.1143/ptps.145.113
|View full text |Cite
|
Sign up to set email alerts
|

Level Spectroscopy: Physical Meaning and Application to the Magnetization Plateau Problems

Abstract: We review the level spectroscopy, which is a powerful method of analyzing the numerical data with respect to the Berezinskii-Kosterlitz-Thouless quantum phase transition in one dimension. We focus on its physical meaning and also its application to the magnetization plateau problems. * )

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…(13) As a numerical check, we have also performed the numerical diagonalization using the Lanczös method and the level spectroscopy analysis. [8][9][10][11] We found that the numerical results are in good agreement with the results of the perturbation theory as shown in Figs.3-8.…”
supporting
confidence: 84%
“…(13) As a numerical check, we have also performed the numerical diagonalization using the Lanczös method and the level spectroscopy analysis. [8][9][10][11] We found that the numerical results are in good agreement with the results of the perturbation theory as shown in Figs.3-8.…”
supporting
confidence: 84%
“…For the purpose of drawing the M = (2/3)M s plateau phase diagram, we have performed the numerical diagonalization of the finite size Hamiltonian by the Lanczos method. We can apply the LS method [19,26,27,34,35] to this kind of plateaufulplateauless transition of the BKT type [36,37,38,39] …”
Section: Magnetization Plateau At M = (2/3)m Smentioning
confidence: 99%
“…Amongst those, the most remarkable one is the necessity to understand the unusual new properties presented by low dimensional magnetic materials [1,2,3,4] at low temperature, which are described in terms of its many-body behaviour and its quantum transitions [5]. As manifestation of these properties we can mention the appearance of magnetization plateaus as functions of the external magnetic field [6,7], the existence of an energy gap between the ground state and first excited state at zero field [8] and the presence of quantum critical behaviour [4,9,10].…”
Section: Introductionmentioning
confidence: 99%